Narratives and displays: a critical examination of cultural frames in exhibiting ‘Awakenings: Art in Society in Asia 1960s-1990s’ - Kirk, Stephanie Morgan (Nanyang Technological University, 2022)
This thesis explores how the presentation of the exhibition Awakenings: Art in Society in Asia 1960s-1990s was adapted to its specific context between each iteration. Awakenings was jointly organized by National Gallery Singapore, The National Museum of Modern and Contemporary Art in Korea, the National Museum of Modern Art Tokyo and the Japan Asia Foundation Centre. One of the curator’s goals was to decentre art histories. This was achieved through a symposium in early development and by focusing on the thematic similarities in art and social movements across in Asia and building a methodology independent from the western cannon and Euro-American art history. However, in this exhibition the local context remains relevant pertaining to the display and narrative exhibited in each location as they were slightly altered to suit context-specific values, expectations and agendas. This thesis asks: how did the specific cultural contexts play a role in shaping the exhibition narrative and presentation between the three locations; Singapore, Japan and Korea? It draws on press and academic reviews, archival material including catalogues, as well as interviews with the head curators of the Awakenings exhibition. The results were explored through Geert Hofstede’s Cultural Dimension’s Theory to compare and contrast how different audiences, agendas and social norms played a role in specifying the exhibition. Due to time and availability limitations, sufficient data for discussion was only gathered for the National Gallery Singapore iteration. The results show how curators negotiate agendas, connect with their audience interests and the curator’s hopes for the extending the life of Awakenings through travel to Euro-America and extensive archives. This thesis contributes to the discourse around curatorial narratives and methodologies in non-western contexts as well as engages with the nuances and challenges of curating art within Singaporean institutions